Reduced energy density of close‐up diets decrease ruminal pH and increase concentration of volatile fatty acids postpartum in Holstein cows. (27th June 2017) - Huang, Wenming; Tian, Yujia; Li, Shengli; Wu, Zhaohai; Cao, Zhijun
Abstract: The objective of this study was to determine the effect of reduced energy density of close‐up diets on ruminal fermentation parameters in transition cows. Fourteen Holstein dry cows were blocked and assigned randomly to three groups fed a high energy density diet (HD, 1.62 Mcal of net energy for lactation (NEL )/kg dry matter (DM)), or a middle energy density diet (MD, 1.47 Mcal NEL /kg DM), or a low energy density diet (LD, 1.30 Mcal NEL /kg DM) prepartum, and were fed the same diet postpartum. The reduced energy density diets decreased the average dry matter intake (DMI) prepartum and tended to increase the DMI postpartum. The ruminal pH of the LD group was significantly higher prepartum and lower during the first week of lactation compared with the other two groups. The reduced energy density diet depressed the average ruminal concentration of propionate and butyrate prepartum, and increased the average concentration of total volatile fatty acids (VFA) postpartum. The LD group had higher populations of Butyrivibrio fibrisolvens and Ruminococcus flavefaciens relative to HD and MD groups on 7 days in milk. In conclusion, the cows fed reduced energy density diet prepartum had higher VFA concentration, but were more susceptible to subacute ruminal acidosis postpartum.